1995
DOI: 10.1177/104063879500700419
|View full text |Cite
|
Sign up to set email alerts
|

Lead Poisoning and Toxicokinetics in a Heifer and Fetus Treated with CaNa2EDTA and Thiamine

Abstract: Abstract. Lead (Pb) poisoning of a pregnant heifer was diagnosed based upon clinical signs (head pressing, blindness, muscle twitching) and a blood lead concentration of 1.73 ppm. Blood and urinary Pb half-lives with CaNa 2 EDTA/thiamine therapy were determined to be 2.08 and 1.38 days, respectively. Many cations (Ca, Fe, Zn, Na, Cu), including Pb, were excreted at higher concentrations in urine during therapy. Blood (0.425 ppm) and liver (4.85 ppm) Pb concentrations in the fetus were 71.7% and 84.3% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…Analysis of results of the study reported here confirm those of other studies 3,5 in that they document that young, milk-fed calves are highly susceptible to lead toxicosis, as evidenced by the fact that within 10 days after initiation of oral administration of lead doses, all lead-treated calves developed several clinical signs compatible with lead intoxication. Furthermore, statistical analysis revealed that tissue lead concentrations of lead-exposed calves were significantly higher than those of control calves of group 1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Analysis of results of the study reported here confirm those of other studies 3,5 in that they document that young, milk-fed calves are highly susceptible to lead toxicosis, as evidenced by the fact that within 10 days after initiation of oral administration of lead doses, all lead-treated calves developed several clinical signs compatible with lead intoxication. Furthermore, statistical analysis revealed that tissue lead concentrations of lead-exposed calves were significantly higher than those of control calves of group 1.…”
Section: Discussionsupporting
confidence: 92%
“…[1][2][3][4] Major clinical signs of lead toxicosis in cattle relate to the gastrointestinal tract or CNS and can include initial constipation followed by diarrhea (which may contain blood), abdominal pain, weak or abolished rumen motility, blindness, ataxia, dullness, lethargy, muscle fasciculations, and convulsions. 4,5 In other studies, [5][6][7] investigators have documented that extremely low doses of lead are capable of causing lead toxicosis in young milk-fed calves and susceptibility of such calves can be considerably affected by diets containing hay or grain.…”
mentioning
confidence: 99%
“…Values were recorded as parts per million (ppm) wet weight (ww). Quality assurance and quality control were followed as in O'Hara et al (1995).…”
Section: Heavy Metal Analysismentioning
confidence: 99%
“…Histopathology of the brain will show evidence of polioencephalomalacia, such as cerebral laminar cortical necrosis, severe congestion of cerebrocortical tissue and meninges, edema, and endothelial swelling. 85,86 Severe liver necrosis and lipid accumulation, 81 and renal tubular degeneration, 82 may occur. Ante-mortem diagnosis of acute intoxication relies on history of exposure, clinical signs, and blood lead concentration greater than 0.35 µg/mL.…”
Section: Leadmentioning
confidence: 99%
“…Ante-mortem diagnosis of acute intoxication relies on history of exposure, clinical signs, and blood lead concentration greater than 0.35 µg/mL. 85 It is critical to analyze a whole blood sample for lead. Serum and plasma samples are not appropriate for lead analysis because lead associated with red blood cells.…”
Section: Leadmentioning
confidence: 99%